The early administration of Lactobacillus reuteri DSM 17938 controls regurgitation episodes in full-term breastfed infants. (August 2014) - Garofoli, Francesca; Civardi, Elisa; Indrio, Flavia; Mazzucchelli, Iolanda; Angelini, Micol; Tinelli, Carmine; Stronati, Mauro
Abstract Forty breastfed full-term infants were randomly, double blind assigned to receive orally Lactobacillus reuteri (L. reuteri) DSM 17938, 5 drops/daily (108 colony-forming units), for 4 weeks (n = 20) or an identical placebo (n = 20), starting before third day of life. They underwent basal and final visit to monitor growth parameters and gastrointestinal (GI) disease. Parents registered daily: crying minutes, stool frequency and consistency, numbers of regurgitations, adverse events. Secretory IgA (sIgA) has been measured in saliva on 28th day. Treated infants demonstrated a reduction in daily regurgitations at the end of treatment (p = 0.02), three neonates in the placebo group only needed simethicone for GI pain, sIgA level was similar in both groups. Random casualty produced an unbalanced gender distribution in the groups, but this bias did not affect the results. Therefore, early administration of L. reuteri DSM 17938 resulted beneficial in preventing regurgitation episodes during the first month of life.